Monoamine oxidase A and B inhibitory activities of 3,5-diphenyl-1,2,4-triazole substituted [1,2,4]triazolo[3,4-b][1,3,4]thiadiazole derivatives - (:unkn) unknown (Academic Press Inc., 2022)
Monoamine oxidase (EC 1.4.3.4, MAO) is a flavin adenine dinucleotide-containing flavoenzyme located on the outer mitochondrial membrane and catalyzes the oxidative deamination of monoaminergic neurotransmitters and dietary amines. MAO exists in humans as two isoenzymes, hMAO-A and hMAO-B, which are distinguished by their tertiary structures, preferred substrates and inhibitors, and selective inhibition of these isoenzymes are used in the treatment of different diseases such as Alzheimer's, Parkinson's and depression. In the present study, we report the design, synthesis and characterization of 3,5-diphenyl-1,2,4-triazole substituted [1,2,4]triazolo[3,4-b][1,3,4]thiadiazole derivatives as novel and selective inhibitors of hMAO-B. Twenty one compounds (38, 39a-h, 41a-d, 42a-h) were screened for their inhibitory activity against hMAO-A and hMAO-B by using in vitro Amplex Red® reagent based fluorometric method and all compounds were found to be as selective h-MAO-B inhibitors to a different degree. The compound 42e and 42h displayed the highest inhibitory activity against hMAO-B with IC50 values of 2.51 and 2.81 µM, respectively, and more than 25-fold selectivity towards inhibition of hMAO-B. A further kinetic evaluation of the most potent derivative (42e) was also performed and a mixed mode of inhibition of hMAO-B by the compound 42e was determined (Ki = 0,26 µM). According to our findings the [1,2,4]triazolo[3,4-b][1,3,4]thiadiazole emerged as a promising scaffold for the development of novel and selective hMAO-B inhibitors. © 2021 Elsevier Inc.
Keywords: 1,2,4-Triazoles; 1,3,4-thiadiazoles; Monoamine oxidases; Triazolothiadiazoles